Macrofauna inhabiting the sponge Paraleucilla magna (Porifera: Calcarea) in Rio de Janeiro, Brazil. (7th June 2012) - Padua, André; Lanna, Emilio; Klautau, Michelle
Abstract : Sponges (phylum Porifera) are important components of the benthic marine fauna known for their interactions with vertebrates and a large sort of invertebrates seeking for food, shelter or substrate for attachment. Studies on this subject, however, were restricted only to the macrofauna inhabiting sponges of the class Demospongiae. In the present work, we describe the macrofauna associated with a calcareous sponge in Brazil, Paraleucilla magna . Individuals of this allegedly non-native species were monthly collected during one year in Rio de Janeiro (Brazil). Fifty taxa representing 10 animal phyla were found associated with P. magna . The most frequent and abundant taxa were Crustacea, Mollusca, Polychaeta and Bryozoa, while echinoderms, cnidarians, ascidians, nemerteans, platyhelminthes and sponges were less frequent or even rare and less abundant. Juveniles of several taxa and pregnant females of Crustacea were found associated with P. magna, but these associations were not exclusive. The macrofauna associated with P. magna did not present a clear seasonality, although it was possible to observe a change in the community composition alongside the year. The volume of the sponges was significantly related to the diversity index (H′) and number of taxa, but not with evenness (J′) and number of individuals. Our results show that P. magna is used as a substrate for attachment and/or shelter by its associates and that most of these associations are just opportunistic. The data presented here reiterate a previous proposal that sponges are important biodiversity reservoirs and that they should be seriously considered in conservation programmes.